Ultra-weak chemiluminescence enhanced by facilely synthesized nitrogen-rich quantum dots through chemiluminescence resonance energy transfer and electron hole injection. Issue 41 (9th May 2017) - Zheng, Yongzan; Zhang, Dingkun; Shah, Syed Niaz Ali; Li, Haifang; Lin, Jin-Ming
Abstract : In this study, a novel nitrogen-rich dots were easily synthesized with high percentage of nitrogen and exhibited unique CL property. Abstract : In this study, novel nitrogen-rich quantum dots (N-dots) were easily synthesized with a very high percentage of nitrogen (about 57%). The N-dots exhibited unique optical properties, which significantly enhanced (400 fold) the ultra-weak chemiluminescent reaction of NaIO4 with H2 O2 via CRET and electron hole injection.